National trends in beverage consumption in children from birth to 5 years: analysis of NHANES across three decades - Fulgoni Victor L; Quann Erin E (Nutrition Journal, 2012)
Abstract Background Given the epidemic of childhood obesity, it is crucial to assess food and beverage intake trends. Beverages can provide a large number of calories and since consumption patterns seem to develop at a young age we examined beverage consumption trends over three decades. The objective of this study was to assess the beverage (milk, fruit juice, fruit drinks, tea, soy beverages, and soft drinks) consumption trends in children <1-5 years of age. Methods Data from individuals ages <1-5 years participating in the National Health and Nutrition Examination Survey (NHANES) from 1976–1980, 1988–1994 and 2001–2006 were used to assess beverage consumption and associated calorie and nutrient intakes. Results During the NHANES 1976–1980 and 1988–1994 periods, approximately 84–85% of children were consuming milk, whereas only 77% were consuming milk during NHANES 2001–2006. Flavored milk intake was relatively low, but increased to 14% during the last decade (p < 0.001). Fruit juice consumption increased dramatically during NHANES 2001–2006 to more than 50% of the population compared to about 30% in the older surveys (p < 0.001). No significant changes were observed in fruit drink intake across all three decades with 35-37% of this population consuming fruit drinks. At least 30% of children consumed soft drinks. Milk was the largest beverage calorie contributor in all three decades surveyed and was the primary contributor of calcium (52-62%), phosphorus (37-42%), magnesium (27-28%), and potassium (32-37%). Fruit juice and fruit drinks each provided 8-10% of calories with soft drinks providing 5-6% of calories. Fruit juice was an important provider of potassium (16-19%) and magnesium (11%). Fruit drinks provided less than 5% of nutrients examined and soft drinks provided very little of the nutrients evaluated. Conclusions Given concerns about childhood obesity and the need to meet nutrition requirements, it is prudent that parents, educators and child caretakers replace some of the nutrient poor beverages young children are currently consuming with more nutrient dense sources like low-fat and fat-free milk.